2017
DOI: 10.1007/s40279-017-0726-y
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Return to Sports Activities and Work After Osteotomies Around the Knee: A Systematic Review and Meta-Analysis

Abstract: BackgroundKnee osteotomies are proven treatment options, especially in younger patients with unicompartmental knee osteoarthritis, for certain cases of chronic knee instability, or as concomitant treatment for meniscal repair or transplantation surgery. Presumably, these patients wish to stay active. Data on whether these patients return to sport (RTS) activities and return to work (RTW) are scarce.ObjectivesOur aim was to systematically review (1) the extent to which patients can RTS and RTW after knee osteot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
3
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(115 citation statements)
references
References 65 publications
8
96
3
8
Order By: Relevance
“…The procedure provides both an offloading component as well as a more favourable mechanical environment in the presence of ligament laxity. In our young patient cohort, the return to work rate was 93%, which is comparable with the highest reported rates in the literature 32. Evidence on the possibility of returning to professional or competitive levels of sports following knee osteotomy is sparse.…”
Section: Discussionsupporting
confidence: 81%
“…The procedure provides both an offloading component as well as a more favourable mechanical environment in the presence of ligament laxity. In our young patient cohort, the return to work rate was 93%, which is comparable with the highest reported rates in the literature 32. Evidence on the possibility of returning to professional or competitive levels of sports following knee osteotomy is sparse.…”
Section: Discussionsupporting
confidence: 81%
“…This is remarkable given the importance of participation in sports and work for patients after orthopaedic surgery,5 6 especially for patients who are of working age for whom resumption of societal participation is an important treatment goal. Moreover, return to sports and work is typically delayed and/or not successful for many of these patients 7–11. For instance, patients undergoing joint replacement surgery considered advice regarding participation to be inconsistent and not tailored to their individual circumstances, which often left them with the feeling that they would have been able to recover sooner than what they had actually accomplished 5…”
Section: Introductionmentioning
confidence: 99%
“…The current literature on the topic of RTS for patients receiving isolated correctional osteotomies of the knee has included heterogeneous populations, mostly focusing on patients receiving valgus-inducing osteotomies. 13 To our knowledge, only 1 previous study has analyzed physical activity after DFVO for lateral compartment knee OA. De Carvalho et al 38 reported on 26 patients who received a DFVO at 48 months' follow-up, only 15 (57.7%) of whom had performed routine physical activity preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Recent improvements in operative techniques, surgical devices, and evidence-based treatment guidelines have allowed for realignment procedures and MAT to be performed in combination. 13 Previous studies have shown that MAT and realignment osteotomies, when performed in combination, provide clinically meaningful patient improvements at short-and long-term follow-up. 5,14 However, these studies are heterogeneous in terms of indications and techniques because they included patients with either medial or lateral compartment pathology due to valgus or varus malalignment.…”
Section: See Commentary On Page 261mentioning
confidence: 99%